Credit availability in the crisis: which role for the European Investment Bank Group? - Alessandro Fedele; Andrea Mantovani; Francesco Liucci (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
In this paper we consider a moral hazard problem between a creditworthy firm which needs funding and a bank. We first study under which conditions the firm does not obtain the loan. We then determine whether and how the intervention of an external financial institution can facilitate the access to credit. In particular, we focus on the European Investment Bank Group (EIBG), which provides (i) specific credit lines to help banks that finance small and medium-sized enterprises (SMEs)and (ii) guarantees for portfolios of SMEs'loans. We show that only during crises the EIBG intervention allows to totally overcome the credit crunch.
Keywords: G01; D82; D21; 330